A Revised Code of Ordinances of the City of Tuscaloosa (1885) Using fire-arms while fighting in a public place, § 330 - (:unkn) unknown (General Publisher, 1885)
SEC. 636. Any minor having in his possession, or using any pistol of any kind described in section 635, shall, on conviction, be fined not less than one nor more than one hundred dollars.
--
Keywords: DUELING